Monitoring soil erosion on agricultural land: results and implications for the Rother valley, West Sussex, UK. Issue 15 (13th October 2020) - Boardman, John; Burt, Tim; Foster, Ian
Abstract: Monitoring has played a key role in understanding the rates, extent and frequency of erosion on agricultural land and this includes projects in Switzerland, Germany and the UK. In this case we focus on highly erodible soils in the Rother valley, West Sussex, southern England on which grow a range of arable crops throughout the year. Erosion rates and extent are high, particularly in response to exceptionally wet periods in the early winter. In the monitored period, rates on summer crops were relatively low due to an absence of intense summer storms. In the years 2015–2020, erosion was localized to where limited areas of bare ground coincided with heavy winter rainfall. Issues of river pollution, associated with excessive sedimentation, off‐site flooding and a high degree of connectivity between arable fields and the river, are of increasing concern. Mitigation measures need to be expanded to protect freshwater systems and properties. This study has implications for similar programmes in intensely farmed regions. © 2020 John Wiley & Sons, Ltd. Abstract : We describe a five‐year soil erosion monitoring programme in the Rother valley, UK. Monitoring is based on field observations and measurement, and remote sensing. The project is set in the context of over 20‐years of erosion data for almost 200 arable fields. Occasional episodes of serious erosion lead to muddy flooding and river pollution.